2019
DOI: 10.1016/j.radonc.2019.03.026
|View full text |Cite
|
Sign up to set email alerts
|

MRI-only brain radiotherapy: Assessing the dosimetric accuracy of synthetic CT images generated using a deep learning approach

Abstract: Purpose: This study assessed the dosimetric accuracy of synthetic CT images generated from magnetic resonance imaging (MRI) data for focal brain radiation therapy, using a deep learning approach. Material and Methods:We conducted a study in 77 patients with brain tumors who had undergone both MRI and computed tomography (CT) imaging as part of their simulation for external beam treatment planning. We designed a generative adversarial network (GAN) to generate synthetic CT images from MRI images. We used Mutual… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
102
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(112 citation statements)
references
References 30 publications
7
102
0
Order By: Relevance
“…Magnetic resonance imaging (MRI) has superior soft tissue contrast over computed tomography (CT), allowing for improved organ‐at‐risk segmentation and target delineation for radiation therapy treatment planning . Since dose calculation algorithms rely on electron density maps generated from CT images for calculating dose, MRIs are typically registered to CT images and used alongside the CT image for treatment planning . However, the CT/MRI registration process has inherent errors, for example, a geometrical uncertainty of approximately 2 mm is present in cranial MRI .…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) has superior soft tissue contrast over computed tomography (CT), allowing for improved organ‐at‐risk segmentation and target delineation for radiation therapy treatment planning . Since dose calculation algorithms rely on electron density maps generated from CT images for calculating dose, MRIs are typically registered to CT images and used alongside the CT image for treatment planning . However, the CT/MRI registration process has inherent errors, for example, a geometrical uncertainty of approximately 2 mm is present in cranial MRI .…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, some methods of synthetic CT generation may require nonstandard sequences that increase measurement time [27]. Deep learning-based approaches are at the forefront of current research on synthetic CT and have been shown to outperform other published approaches in terms of mean absolute HU errors in a recent study [28]. These solutions could allow for fast and robust synthetic CT generation from standard MR sequences.…”
Section: Promises Of Synthetic Ct and Mr-only Planningmentioning
confidence: 99%
“…Recent advances in DNN and specifically in GANs have enabled innovations in creating a new image or composing a symphony . This discovery paradigm can be applied to various materials and provided thoughtful guidance to the synthesis of new materials . GAN is one of the nonparametric approaches for deep generative models initially proposed by Goodfellow et al The generative models can be used to create plausible molecular structures for high‐throughput screening, which is the first step in molecular discovery.…”
Section: Molecular Discoveries Using Gansmentioning
confidence: 99%